EFEKTIVITAS PENGGUNAAN GOOGLE CLASSROOM DALAM MATA PELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN (PJOK) DI KELAS XI IPA SMAN 1 BINTAN UTARA - Kevin Pratama; Agus Sulastio; Agus Prima Aspa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The problem in this research was due to the outbreak of the Corona virus (Covid-19) in Indonesia in early 2020. The government tried to prevent the spread of the Corona virus outbreak through the community activities on various aspects, including education, to limit. Because of this policy, schools all over Indonesia are implementing distance learning or drop off using Google Classroom media. The aim of this research was to